Does Hormone Replacement Normalize Bone Geometry in Adolescents With Anorexia Nervosa?. (January 2014) - DiVasta, Amy D; Feldman, Henry A; Beck, Thomas J; LeBoff, Meryl S; Gordon, Catherine M
ABSTRACT Young women with anorexia nervosa (AN) have reduced secretion of dehydroepiandrosterone (DHEA) and estrogen contributing to skeletal deficits. In this randomized, placebo‐controlled trial, we investigated the effects of oral DHEA + combined oral contraceptive (COC) versus placebo on changes in bone geometry in young women with AN. Eighty women with AN, aged 13 to 27 years, received a random, double‐blinded assignment to micronized DHEA (50 mg/day) + COC (20 µg ethinyl estradiol/0.1 mg levonorgestrel) or placebo for 18 months. Measurements of areal bone mineral density (aBMD) at the total hip were obtained by dual‐energy X‐ray absorptiometry at 0, 6, 12, and 18 months. We used the Hip Structural Analysis (HSA) program to determine BMD, cross‐sectional area (CSA), and section modulus at the femoral neck and shaft. Each measurement was expressed as a percentage of the age‐, height‐, and lean mass‐specific mean from an independent sample of healthy adolescent females. Over the 18 months, DHEA + COC led to stabilization in femoral shaft BMD (0.0 ± 0.5% of normal mean for age, height, and lean mass/year) compared with decreases in the placebo group (−1.1 ± 0.5% per year, p = 0.03). Similarly, CSA, section modulus, and cortical thickness improved with treatment. In young women with AN, adrenal and gonadal hormone replacement improved bone health and increased cross‐sectional geometry. Our results indicate that this combination treatment has a beneficial impact on surrogate measures of bone strength, and not only bone density, in young women with AN. © 2014 American Society for Bone and Mineral Research.